If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6 = -48 + -4x Reorder the terms: 6 + 5x = -48 + -4x Solving 6 + 5x = -48 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 6 + 5x + 4x = -48 + -4x + 4x Combine like terms: 5x + 4x = 9x 6 + 9x = -48 + -4x + 4x Combine like terms: -4x + 4x = 0 6 + 9x = -48 + 0 6 + 9x = -48 Add '-6' to each side of the equation. 6 + -6 + 9x = -48 + -6 Combine like terms: 6 + -6 = 0 0 + 9x = -48 + -6 9x = -48 + -6 Combine like terms: -48 + -6 = -54 9x = -54 Divide each side by '9'. x = -6 Simplifying x = -6
| 2x^2-25x-72= | | 26x+17=5(5x+1) | | 9x^2+8x-9=8x | | 4x-4-8y+8-5y= | | 2x+3y=5x-2y-4y | | 15+5c-2=29 | | 38+[23-(13+10)]= | | 5x+6=48-4x | | y*y=36 | | 1000x=(1000x-1x) | | 3m+g=2k | | 0.4y+0.7=0.2-0.1y | | -2k-3=19 | | 6x-5+1=-13 | | -7=-8 | | 198=90+x+5x | | 3x-([-5x]-11)=(-197) | | 5y+8=38 | | S=2(pie)rh | | 7(a+1)-3a=5+4(a-1)2 | | 2x+y=(-9) | | 66.6(6j+9)=3j+7 | | 7x=-1.60 | | -2(z+4)=-(z-5) | | 6(3n+4)=7(8n+4)+7 | | 3a+12=343 | | x-8-2(x+1)=-10 | | -2(3t-4)+4t=8t-9 | | 6(x-15)=3(14+x) | | 2(x+2)-4x=5(x-1) | | 3w-5(w-6)=2(10-w) | | 2(x+6)+(x+2)(x-2)=2x+8 |